Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s10858-020-00327-9
|View full text |Cite
|
Sign up to set email alerts
|

NMR quality control of fragment libraries for screening

Abstract: Fragment-based screening has evolved as a remarkable approach within the drug discovery process both in the industry and academia. Fragment screening has become a more structure-based approach to inhibitor development, but also towards development of pathway-specific clinical probes. However, it is often witnessed that the availability, immediate and longterm, of a high quality fragment-screening library is still beyond the reach of most academic laboratories. Within iNEXT (Infrastructure for NMR, EM and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Ligand quality control is a recognised problem in screening campaigns stemming from a multitude of factors, including the exact amount of compounds provided by vendors, storage conditions, and ligand degradation and aggregation in aqueous buffers, among others (Lepre 2011 ). A recent study aiming to develop a robust fragment library for high-throughput screening reported that up to approximately 30% of fragments failed to pass one or more quality-control metrics, including ligand concentration (Sreeramulu et al 2020 ). Our own experience with bespoke M pro ligands was that ~ 20% of compounds had low or very low effective concentration in solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand quality control is a recognised problem in screening campaigns stemming from a multitude of factors, including the exact amount of compounds provided by vendors, storage conditions, and ligand degradation and aggregation in aqueous buffers, among others (Lepre 2011 ). A recent study aiming to develop a robust fragment library for high-throughput screening reported that up to approximately 30% of fragments failed to pass one or more quality-control metrics, including ligand concentration (Sreeramulu et al 2020 ). Our own experience with bespoke M pro ligands was that ~ 20% of compounds had low or very low effective concentration in solution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is generally no strict pooling strategy for fluorine-based fragments, and the number could be safely extended to more than 20 per group [ 76 , 77 ]. After fragment library construction, it is important to take the quality control into accounts for maintaining the quality of the compound library [ 78 ]. Normally, the compounds dissolved in DMSO- d 6 are suggested to be stored in a freezer (−20 °C), and the frequency for freeze-thaw cycles should better be controlled.…”
Section: Nmr In Fragment-based Drug Discoverymentioning
confidence: 99%
“…At the BMRZ, optimized workflows to support technical assistance to fragment screening by NMR have been developed. These include quality control and solubility assessment of the fragment library 9 , buffer optimization for the chosen targets, 1…”
Section: Introductionmentioning
confidence: 99%